2008
DOI: 10.1177/1352458508092808
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine for multiple sclerosis

Abstract: We analyzed characteristics, motivation, and effectiveness of complementary and alternative medicine in a large sample of people with multiple sclerosis. A 53-item survey was mailed to the members of the German Multiple Sclerosis Society, chapter of Baden-Wuerttemberg. Surveys of 1573 patients (48.5 +/- 11.7 years, 74% women, duration of illness 18.1 +/- 10.5 years) were analyzed. In comparison with conventional medicine, more patients displayed a positive attitude toward complementary and alternative medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 25 publications
7
52
2
Order By: Relevance
“…Physical activity is associated with numerous benefits, but people with MS are still largely inactive and sedentary. The results of this study may ultimately facilitate the promotion of increased physical activity among people with MS. o people with MS was consistent with the previous and current rates of yoga practice (7% and 5%, respectively) found in a large descriptive study of complementary and alternative medicines in MS. 16 The infrequency of swimming is consistent with the rate of about 8% reported in a sample of older adults with a degenerative neurologic disease.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Physical activity is associated with numerous benefits, but people with MS are still largely inactive and sedentary. The results of this study may ultimately facilitate the promotion of increased physical activity among people with MS. o people with MS was consistent with the previous and current rates of yoga practice (7% and 5%, respectively) found in a large descriptive study of complementary and alternative medicines in MS. 16 The infrequency of swimming is consistent with the rate of about 8% reported in a sample of older adults with a degenerative neurologic disease.…”
Section: Discussionsupporting
confidence: 83%
“…Swimming, for example, is a nonweightbearing activity that can increase aerobic capacity while avoiding possible complications of overheating in thermosensitive people with MS. Yoga, as another example, is a mind-body approach that emphasizes meditation, breathing, and postures and has been reported to be very beneficial for people with MS. 16 Future research might examine reasons why swimming and yoga are significantly less common than other physical activities in people with MS. Such reasons may include the inconvenience of accessing a pool and/or the cost of attending yoga classes.…”
Section: Discussionmentioning
confidence: 99%
“…PwMS are interested in dietary intervention as is evident by a German study that showed 41% of PwMS use some dietary intervention for MS [11]. A Cochrane review in 2012, however, concluded that more research is needed to assess the effectiveness of dietary interventions in MS and recommended that PwMS should not focus on a specific diet or supplementation but rather focus on overall healthy eating habits [12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus there may be recruitment bias. Of note, several patients with multiple sclerosis receive IG, which is in line with a dedicated survey in Germany in which 7% of 1,573 patients stated that they had been treated with IG at some time point (Schwarz et al 2008). However, despite some small early trials that have shown some efficacy of IVIG in relapsing-remitting MS, this could not be reproduced in a recent placebo-controlled trial (Cohen 2008;Fazekas et al 2008).…”
Section: Interim Analysismentioning
confidence: 84%